Changing Priority of Industrial Activities in Sistan and Baluchestan Province (Application of Input-output Table) - Esfandiari, Marziyeh; Keikha, Gholamreza (International Journal of Economics and Financial Issues, 2017)
Given the Iranian economic vulnerability channels, strengthening the economy requires to develop production-oriented regional development plans as well as people-based and knowledge-based plans which are relied on domestic intermediate and capital goods. In order to prepare regional development plans according to resistive economy policies, the present study investigated changing ranking of industrial activities over the years 2005, 2009 and 2013 through integrating factor analysis method and numerical taxonomy, highlighting internal interactions of industrial activities and the interactions between industry sector and national economy. For this purpose, input-output table of Sistan and Balouchestan Province within the mentioned years was calculated by augmented Flegg’s location quotient method. Given the findings, “production of food products and a variety of beverages and tobacco,” “production of other non-metallic mineral products” and “production of basic metals” have experienced a growing degree of enjoyment within the studied years. Although quantitative objectives development for the industry section of Iran and thereby the provinces has not been considered in the fourth and fifth development plans to specify its achievement percentage, our findings-based priorities show alignment of the province’s industry sector orientation and performance with the country’s. Keywords: Prioritization, Numerical Taxonomy, Factor Analysis, Input-output Table JEL Classifications: E37, E32